Notulae ad floram Sloveniae - Dakskobler, Igor (Hladnikia (Ljubljana), 1996)
New, up to now northernmost locality of the Illyrian endemic
Keywords: endemic species; endemiti; fitogeografija; flora; florae; phytogeography; Slovenia; Slovenija; vegetacija; vegetation